Malassezia sp. Infection Prevalence in Dermatitis Dogs in Badung Area - Sudipa, Putu Henrywaesa; Pasek Gelgel, Ketut Tono; Jayanti, Putu Devi (Advances in Tropical Biodiversity and Environmental Sciences, 2021)
Malasseziosis is a common fungal infection in dogs and it is secondary to the initial underlying dermatitis infection. These infections can worsen the prognosis of disease in dogs. The study was conducted on 26 dogs that were treated in several veterinary clinics in the Badung, Bali. This study aimed to determine the incidence rate of Malassezia sp. in dogs with dermatitis. Samples were collected using tape smear method from the skin lesion and then by microscopic examination. The results were tabulated and analyze descriptively. The results showed that 15 of the 26 samples of dogs tested positive were infected with Malassezia sp. (58%). Infection is more common in male (60%) and geriatric dogs (40%). Lesions were more common in the ear, limb, vaginal and inguinal region of infected dogs